Ferroptosis: a new strategy for cardiovascular disease - Wang, Yuyuan; Wu, Junduo (Frontiers in Cardiovascular Medicine, 2023)
Cardiovascular disease (CVD) is currently one of the prevalent causes of human death. Iron is one of the essential trace elements in the human body and a vital component of living tissues. All organ systems require iron for various metabolic processes, including myocardial and skeletal muscle metabolism, erythropoiesis, mitochondrial function, and oxygen transport. Its deficiency or excess in the human body remains one of the nutritional problems worldwide. The total amount of iron in a normal human body is about 3–5 g. Iron deficiency may cause symptoms such as general fatigue, pica, and nerve deafness, while excessive iron plays a crucial role in the pathophysiological processes of the heart through ferroptosis triggered by the Fenton reaction. It differs from other cell death modes based on its dependence on the accumulation of lipid peroxides and REDOX imbalance, opening a new pathway underlying the pathogenesis and mechanism of CVDs. In this review, we describe the latest research progress on the mechanism of ferroptosis and report its crucial role and association with miRNA in various CVDs. Finally, we summarise the potential therapeutic value of ferroptosis-related drugs or ferroptosis inhibitors in CVDs.